Cuban Agriculture Before 1959: The Political and Economic Situations - José Alvarez (EDIS, 2004)
Cubans fought for their independence from Spain for most of the nineteenth century. Since most of the armed struggles took place in the countryside and the majority of the fighters were rural inhabitants, the agriarian issue was deeply embedded in the republic inaugurated on May 20, 1902. What was the rural reality during the 57 years between 1902 and 1959? Answers appear at both extremes of the political spectrum, exposed and espoused by supporters and detractors of the current Cuban regime. This fact sheet intends to address these conflicting viewpoints by analyzing the available data on pre-1959 rural Cuba. This is EDIS document FE479, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, UF/IFAS, University of Florida, Gainesville, FL. Published July 2004.